Etika Toleransi di Kalangan Remaja Islam dan Kristen di Desa Sibargot Kabupaten Labuhanbatu - Murdia Boru Sihombing (Medan Resource Center, 2021)
This research is the result of research with a policy research flow that aims to describe and understand the ethics of tolerance among muslim and christian youth (case study of sibargot village, Labuhanbatu Regency), using qualitative research methods. The study examines the tolerance carried out by muslim and christian teenagers in applying the correct ethics of tolerance even between religions, then looks for deviant impacts on the application of tolerance Sibargot village, Labuhanbatu Regency. The aim of this research is to find out and understand how to apply the tolerance possessed by teenagers, both muslim and christian, in the community in fostering ethics in accordance with their respective teachings. Implementation activities that are practiced ethics in the application of adolescent tolerance also have an impact on causing goodness if it is in accordance with the basis obtained in the application of morality, especially in terns of behavior patterns, ethics, morals, and actions to respond. So that the tolerance that develops must be in accordance with the right guidance and diligently pay attention to teenagers so that no one does what they like. Therefore, the ethic of tolerance uses the right way in helping the ethic of tolerance of adolescents by means of togetherness, discussion, organization, for inter-religious peace. After getting data in the field that the ethics of tolerance among muslim and christian teenagers in the appicatioan of adolescent ethnis.